Rapid and distinct responses of particulate and mineral-associated organic nitrogen to conservation tillage and cover crops - Jilling, Andrea; Kane, Daniel; Williams, Alwyn; Yannarell, Anthony C.; Davis, Adam; Jordan, Nicholas R.; Koide, Roger T.; Mortensen, David A.; Smith, Richard G.; Snapp, Sieglinde S.; Spokas, Kurt A.; Stuart Grandy, A. (Geoderma, 2020)
[Display omitted] •SOM responded to tillage and cover crops, but patterns varied by site and fraction.•At low-SOM sites, particulate fractions responded most significantly to tillage.•At high-SOM sites, inclusion of cover crops increased silt and clay-associated SOM. Particulate organic matter (POM) is considered an “active” source of nitrogen (N) in cultivated soils, responding readily to management and being more physically accessible to decomposers than mineral-associated forms of organic matter. However, there is increasing evidence that mineral-associated organic matter (MAOM) can also exhibit short-term changes to management that may impact plant and microbial N dynamics. In this study, we investigated how N within soil organic matter fractions responded to three years of tillage and cover crop treatments. We collected soils from a row-crop (maize-soybean rotation) field experiment replicated across three sites in the north central and mid-Atlantic United States: a high-soil organic matter site (3.1% soil organic carbon) in Illinois (IL) and two sites in Michigan (MI) and Pennsylvania (PA) with lower soil organic matter content (1.0% and 1.4% soil organic carbon, respectively). Management treatments included two levels of tillage (chisel plow and ridge tillage) and two levels of cover crop (with and without rye cover crop). Using an optimized sonication method coupled with particle size separation, we isolated and analyzed for N content free POM, occluded POM, a coarse silt fraction, and MAOM. Using partial least squares regression, we also explored broad cross-site relationships between soil organic matter (SOM) fractions, soil N availability, and crop performance. Both particulate and fine fractions responded to tillage and cover crop treatments, but patterns varied by site and fraction. In the low-SOM MI and PA soils, ridge tillage and cover cropping both increased N within POM fractions. The response to ridge tillage was most pronounced, with a 76% and 24% increase in occluded POM N content in MI and PA, respectively. In contrast, at the IL site (high-SOM), the inclusion of cover crops led to higher N, specifically within the fine fractions (coarse silt and MAOM). Cover cropping increased MAOM N content in IL by 24%. When analyzing all sites together, variables associated with fine fractions were more closely associated with N mineralization and crop performance. MAOM can be responsive to short-term management practices and, along with POM, may also be potential sources of N for crops.